Immunohistochemical Expression of the Tumor Suppressor Protein p16INK4a in Cervical Adenocarcinoma - Eleutério Jr, José; Lima, Thiago Silva; Cunha, Maria do Perpétuo Socorro; Cavalcante, Diane Isabelle Magno; Silva, Angélica Maria Holanda (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To evaluate the diagnostic utility of the p16ink4a protein expression as a marker for adenocarcinoma of the cervix.Methods In a cross-sectional study, p16ink4a expression was evaluated in 30 cervical biopsies from patients diagnosed with invasive adenocarcinoma from 2 reference clinics in Brazil, and compared with 18 biopsies of endocervical polyps (control cases). The performance of the tests for p16ink4a was evaluated using a conventional contingency table, and the Kappa (κ) index was used to evaluate the agreement of the marker with the tissue diagnosis.Results In total, 66% of the invasive adenocarcinoma cases were positive for p16ink4a. All of the adenomatous polyps cases used as negative controls were shown to be negative for p16ink4a. The marker showed a high sensitivity and a high negative predictive value. The Kappa index was good for p16ink4a (κ = 0.6).Conclusion Considering the strong association between the p16ink4a marker and the cervical adenocarcinoma, its use represents an important tool for reducing incorrect diagnoses of adenocarcinoma and thereby avoiding overtreatment.
Keywords: p16INK4a; adenocarcinoma; cervix; immunohistochemistry